High-throughput and point-of-care detection of wheat fungal diseases: Potentialities of molecular and phenomics techniques toward in-field applicability - Francesconi, Sara (Frontiers in Agronomy, 2022)
Wheat crop is one of the most cultivated and consumed commodities all over the world. Fungal diseases are of particular concern for wheat cultivation, since they cause great losses and reduced quality, also for the accumulation of toxin compounds into the final product. In this scenario, optimal disease management strategies are a key point to boost food production and sustainability in agriculture. Innovative and point-of-care diagnostic technologies represent a powerful weapon to early detect fungal pathogens and preventively counteract diseases on wheat with the aim to drastically reduce the fungicides as inputs. Indeed, in-field diagnostics devices are fast, sensitive and ready-to-use technologies able to promptly detect a low inoculum concentration even at the pre-symptomatic stage of the disease. Promising isothermal molecular and phenomics-based methods have been developed to detect wheat fungal pathogens directly in the field. Such technologies could be potentially coupled to directly detect the presence of a certain pathogen and to indirectly disclose the plant-pathogen interactions, since spectral-based methodologies detect host perturbations following the infection. The present review reports the main in-field isothermal molecular-based and phenomics-based detection technologies for fungal pathogens in wheat discussing their advantages, disadvantages and potential applications in the near future.